Improving limits of detection. Microdisc versus microcylinder electrodes - Cinková, K; Clark, M; Sokolov, S; Batchelor-McAuley, C; Švorc, Ľ; Compton, R (Wiley, 2016)
The specific apparent capacitance (Farads per unit geometric area) of commercial carbon microdisc electrodes and in-house fabricated carbon microcylinders is studied through the use of cyclic voltammetry. Home-made microcylinder electrodes exhibit lower specific apparent capacitances and as a result facilitate lower limits of detection. We further demonstrate practically how the electroanalytical limit of the detection of solution phase trace oxygen is significantly improved using such microcylinder electrodes. Finally we show that after the degassing of a solution by nitrogen purging even in the most commonly encountered ‘best’ case scenarios approximately tens of μM of oxygen remain present in the electrochemical cell, unobservable by the commercial microdisc electrodes, but detectable with microcylinder electrodes, testifying to their analytical superiority.